Dynamic determinants of access to weapons: Global evidence - Simplice Asongu; Joseph Nnanna (African Governance and Development Institute (AGDI), 2019)
This study investigates the determinants of and persistence in access to weapons using a global sample of 163 countries for the period 2010 to 2015. The empirical evidence is based on Generalised Method of Moments (GMM). Hysteresis in access to weapons is consistently more apparent in countries with below-median levels in access to weapons, compared to their counterparts with above-median levels in access to weapons. The hysteresis hypothesis within this context is the propensity of past values of access to weapons to influence future values of access to weapons. Factors that consistently drive access to weapons are: perceptions of crime; criminality; conflict intensity; political instability; military expenditure, violent demonstrations and terrorism. The effects of these drivers are contingent on initial levels of access to weapons. Policy recommendations for managing access to weapons are discussed.
Keywords: H56; L64; K42; P50; 330; Access to weapons; Global evidence; Persistence; Arms; Security